Cardiovascular magnetic resonance characterisation of the phenotype of resistant uncontrolled hypertension - Letuka, Pheletso (Department of Medicine, 2020)
Background: Resistant hypertension (RH) is defined as blood pressure (BP) that remains elevated (>140/90mmHg) despite being treated with an antihypertensive regimen of 3 or more medications from different classes, including a long-acting calcium channel blocker, an angiotensin converting enzyme inhibitor or angiotension receptor blocker and a diuretic. The prevalence of RH in South Africa is currently unknown, however, clinical reports suggest that it is not rare. Patients with RH are significantly predisposed to cardiovascular (CV) diseases compared to patients with controlled BP. Consequences of RH include left ventricular hypertrophy, heart failure, ischaemic heart disease, chronic kidney disease leading to end-stage renal disease, stroke, vascular dementia, CV death and peripheral arterial disease. A proportion of patients with RH who never achieve BP control despite maximal medical treatment, represent a potentially novel and distinctive phenotype which is different from RH patients whose BP canbe controlled. Recognising and categorising such patients becomes the initial and crucial step in stratifying phenotypes and defining mechanisms of treatment resistance. Objectives: The aim of this study was to identify patients with resistant uncontrolled hypertension (RUH) and compare phenotypes in these patients to resistant controlled hypertensives (RCH). Methods: We enrolled 50 patients from the Groote Schuur Hospital Hypertension Clinic: a teriary referral hospital for RH. Patients on 4 or more antihypertensive medication including a diuretic, with BP< 140/90mmHg were considered RCH, and those with BP ≥ 140/90 considered RUH. Assessments included clinical examination, electrocardiography, echocardiography, applanation tonometry, serum biomarkers and cardiovascular magnetic resonance (CMR - which included biventricular volumes and function, myocardial strain, tissue characteristics and late gadolinium enhancement - LGE). Results: Thirty were diagnosed with RUH and twenty with RCH. Patients with RUH were more likely to have a longer duration since diagnosis of hypertension (10.5±10.7 vs. 3.6±3.4, p=0.02) and more likely to be on treatment that included an ACE-inhibitor (90% vs. 58%, p=0.01). As expected, patients with RUH had significantly higher systolic BP (155.6±21.6 vs. 137.8±16.5 mmHg, p< 0.001), diastolic BP (88.4±14.5 vs. 77.5±13.6 mmHg, p= 0.03), mean arterial BP (115.4±17.2 vs 101±15.3 mmHg, p= 0.004) and pulse pressure (67.3±14.2 vs. 60.1±12.4 mmHg, p=0.001). Further, RUH patients had significantly lower large artery elasticity (12.5±4 vs 14.7±3.8ml/mmHgx100, p=0.08) and lower small artery elasticity (4.1±2.1 vs. 6.9±3.6ml/mmHgx100, p< 0.001). RUH patients also had a higher systemic vascular resistance (1754±418.4 vs. 1363±371.5dyneXsecXcm-5, p=0.002). On CMR, RUH patients had lower right ventricular (RV) end-systolic and end-diastolic volumes (p=0.02), as well as higher indexed left ventricular mass (LVMI) (61.6±17.6 vs 52.9±13.9 g/m2 , p= 0.06). There were no differences in native T1, extracellular volume quantification and LGE volume fraction between RUH and RCH patients. Conclusions: Patients with RUH have a greater involvement and more severe CV phenotype, that is likely to result in increased CV morbidity and mortality, including greater target end organ damage as a result of vascular adaptations and concentric remodeling.